Makeeta elämää - lasten paino ja suunterveys : tutkimustuloksia 1. ja 5. luokan oppilaista LATE-tutkimuksen (2007-2009) aineistosta - Poikonen, Laura (2018)
It’s important to find out reasons to childhood overweight and caries, which increase with age. The aim of the thesis is to determine, based on the research material, whether 1st and 5th class pupils with underweight or overweight have more or less unfavourable oral hygiene habits than their peers with normal weight, and whether snacks with sugar form part of their diet. The analysis variables were chosen in accordance with the research question and the theoretical framework. The research material of this thesis is the data on 1st and 5th class pupils collected by the National Institute for Health and Welfare (THL) in their LATE-study (2007-2009) (n=2105). The material of the LATE-study comprises data collected from ten health stations all over Finland and samples from Turku and the county of Kainuu for a pilot study following children’s and youth’s health (THL 2015). Parents answered to questions. The research methodology includes statistical methods, cross tabulations and Chi-square test and comparison of data tables. The analysis focuses on variables of the research material related to oral health, nutrition and weight. Caries and teeth brushing habits not meeting recommendations, which increases with age, are most prevalent among children with overweight. Underweight girls are the most diligent users of oral health services. Concomitantly, they have also less caries than other weight groups and more regular teeth brushing habits. Difference of statistical significance can be observed between the weight groups of 5th class girls when examining their week day snacking habits (p=0,004). Most prevalent among all 5th class girls are snacking on 1-2 week days. Those with normal weight snack more often on each weekday. None of those with underweight reported snacking on each weekday and of those with overweight also under one of tenth. Underweight girls consume more sweets and sweet foods as snacks and they snack on weekends the most in quantity when compared with the other weight groups.